Kimlik-bellek: ‘istedim ki bilineyim!’ sanatta yeterlik (eser metni) - Korkmaz, Tuba (My University, 2016)
Kimlik ve Bellek, savaşlar ve yarattığı bir sonuç olarak göçlerle, milli kimlik bilinci ve kolektif belleğin sorgulanmasıyla ya da farklı kültürel kimliklerden oluşmuş devletlerin başka bir üst kimlik oluşturma çabasıyla, popüler bir konu olarak günümüzde tartışılmaktadır. Konu, 1980 li yıllardan beri de sanatta bir sorun olarak yerini almıştır. Etnik farklılıklar, ‘öteki’leşme süreçleri, özellikle kadınlarla veya cinsel tercihi farklı olan insanlar aracılığıyla cinsel kimlik konusu da sanat aracılığıyla sorgulanmıştır. Kimlik ve belleği ayrı kavramlar olarak birbirinden kopuk düşünmek ve birbirinden ayrı anmak kavramların tanımlarını eksik bırakır. Kimliğin bellek ile ilişkisi vazgeçilmezdir. Kişinin biriktirdiği anılar ve tecrübeler toplamı aracılığıyla oluşan bellek; kimliği oluşturur. Tez bu ilişkiyi tanımlayacak, sorgulayacak ve sanatsal alanda yeni bir kurguya dönüştürecektir. ‘Kimlik-Bellek Kavramının Günümüz Sanatına Yansımaları’ konulu bu metnin yapıtı ‘İstedim Ki Bilineyim!’ ile farklı seramik teknikleri kullanılarak kimlik ve bellek kavramları yeni bir bağlamda değerlendirilmiş olacaktır. Bellek, Seramik Sanatı, Sanatta Kimlik-Bellek

The Identity and the Memory, is being debated today as a popular subject with the wars and the migrations resulting as a consequence, by querying the national identity consciousness and the collective memory or by the effort to develop another supra-identity of the states that have been comprised of different cultural identities. The subject, has taken its place as a problem in the art since the 1980s. The sexual identity matter has also been questioned through the ethnical differences, the processes of “marginalization”, through especially women or through the people with different sexual preferences. To think about the identity and the memory as the notions separated from each other and to refer them separately leaves the definitions of the notions incomplete.The relationship of the identity with the memory is indispensible. The memory comprises the identity via the summation of the memoirs and the experiences that a person gathers. The thesis shall define, question this relationship and convert it into a new speculation in the field of art. With the work of this thesis “I wished that I be Recognized” with the subject of “The Reflections of the Identity-Memory Concept on the Contemporary Art”, the identity and memory concepts shall be re-evaluated by utilizing different ceramic techniques. Identity, Memory, Ceramic Art, Identity-Memory in the Art
Keywords: Bellek, Sanatta; Kimlik, Sanatta; Seramik sanatı; Türkiye